Biosynthesis, structural characteristics and prebiotic properties of maltitol-based acceptor products. (March 2021) - Hu, Xiuting; Song, Liping; Yang, Yuqi; Wang, Lei; Li, Yungao; Miao, Ming
Graphical abstract: Highlights: Maltitol derivatives were acceptor-action synthesized using alternansucrase. Structural characterization was determined using MS and NMR analysis. Their fermentation selectivity was investigated in-vitro by fecal bacteria. Fermentation of DP4-H produced the highest content of butyrate and SCFAs. Bio-synthesized maltitol-receptor products would be prebiotic ingredient candidates. Abstract: To obtain novel prebiotic candidates, maltitol derivatives were obtained through alternansucrase-catalyzed reaction between sucrose and maltitol and their structural characteristics and in vitro fermentation were investigated. The reaction parameters, including the ratio of sucrose to maltitol, substrate concentration and reaction time, were optimized with the yield of 44.9% as well as 89.6 mg/mL of maltitol derivatives. These maltitol derivatives included α-D-Glc p -(1 → 6) - α-D-Gl cp -(1 → 4)-D-Gol (DP3-H), α-D-Gl cp -(1 → 3) - α-D-Gl cp - (1 → 6) - α-D-Gl cp -(1 → 4)-D-Gol (DP4-H) and α-D-Gl cp -(1 → 6) - α-D-Gl cp -(1 → 3) - α- D-Gl cp -(1 → 6) - α-D-Gl cp -(1 → 4)-D-Gol (DP5-H). Similar to fructooligosaccharides, they showed the prebiotic activity. Specifically, the highest increase of Bifidobacteria was observed in the cultures supplemented with both DP4-H and DP5-H, whereas the most significant proliferation of Lactobacillus occurred in the culture supplemented with DP3-H. Moreover, fermentation of DP4-H resulted in the highest contents of butyrate and total short-chain fatty acids, which might be related to the highest α-(1 → 3) bond content. These results suggested that the maltitol-receptor products via alternansucrase-catalyzed acceptor reaction were the prebiotic ingredient candidates and the prebiotic activity of maltitol derivatives depended on the type of the glycosidic bond.